2021
DOI: 10.1002/kjm2.12392
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐10a‐5p inhibits cell metastasis in hepatocellular carcinoma via targeting SKA1

Abstract: A variety of microRNAs (miRNAs) are involved in the occurrence and development of hepatocellular carcinoma (HCC). However, the role of miR-10a-5p in the progression of HCC remains unclear. Therefore, the purpose of this study was to determine the role of miR-10a-5p in the development of HCC and the possible molecular mechanism. miR-10a-5p expression in HCC tissues and plasma from patients was detected by quantitative real-time polymerase chain reaction. Migratory changes in HCC cells were detected after the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…These relationships provide a potential mechanism on how this lncRNA contributes to the downregulation of mRNAs ( Table 2 ). In the s iOCT4-POVPC vs. siOCT4-DMSO groups, downregulated ENSMUST00000173605 had three predicted binding sites for mmu-miR-10a-5p/mmu-miR-10b-5p, and two predicted sites for mmu-miR-15a-5p/mmu-miR-15b-5p and mmu-miR-30a-5p (all upregulated miRNAs), which were reported to regulate cell migration and apoptosis ( Shen et al, 2021 ; Li et al, 2022 ; Chen et al, 2020 ), and phagocytosis ( Cho et al, 2019 ; Murinello et al, 2019 ) and were associated with downregulated mRNAs ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…These relationships provide a potential mechanism on how this lncRNA contributes to the downregulation of mRNAs ( Table 2 ). In the s iOCT4-POVPC vs. siOCT4-DMSO groups, downregulated ENSMUST00000173605 had three predicted binding sites for mmu-miR-10a-5p/mmu-miR-10b-5p, and two predicted sites for mmu-miR-15a-5p/mmu-miR-15b-5p and mmu-miR-30a-5p (all upregulated miRNAs), which were reported to regulate cell migration and apoptosis ( Shen et al, 2021 ; Li et al, 2022 ; Chen et al, 2020 ), and phagocytosis ( Cho et al, 2019 ; Murinello et al, 2019 ) and were associated with downregulated mRNAs ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a growing number of miRNAs associated with HCC have been successively confirmed. Shen et al experimentally proved that miRNA-10a-5p acted on SKA1 to inhibit the metastasis of hepatocellular carcinoma cells [ 22 ]. Liu et al demonstrated that miRNA-494 can promote cell proliferation in HCC [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…MMP3 is regulated by various miRNAs [18,19], subsequently facilitating tumor cell invasion and metastasis [15][16][17]. The abnormal expression of miRNAs has been closely associated with processes such as tumor cell invasion and metastasis in osteosarcoma [18,19,[52][53][54]. For example, the increased expression of MMP-3 induces tumor metastasis in osteosarcoma by inhibiting miR-519d [19], and miR-134 reduces osteosarcoma cell invasion and metastasis by targeting MMP-3 in vivo and in vitro [18].…”
Section: Discussionmentioning
confidence: 99%